Pengembangan Pembelajaran Ekonomi Berbasis Nilai Pancasila dan Nilai Budaya Lokal - Polamolo, Cristian; Wahjoedi, Wahjoedi; Soetjipto, Budi Eko; Utomo, Sugeng Hadi (Universitas Negeri Malang, 2023)
The design of economic learning based on pancasila values and local cultural values to improve students’ knowledge, attitudes and economic behavior is the objective in this study. This type of research uses design-based research (DBR), through cooperative learning with the type of student teams achievement division (STAD). The collection of research data was carried out by essay tests, questionnaires and interviews with high school students as respondents. Feasibility testing of product design is validated by experts from State University of Malang, Indonesia including: learning design experts, economic materials, local culture and practitioners. Based on the analysis of factual models, it was found that current economic learning practices have not improved students’ knowledge, attitudes and behavior. The results of validation and testing of learning design prototypes are declared very useful and feasible to be implemented in economic learning in high schools. The results of the study show that economic learning design based on Pancasila values and local cultural values can improve knowledge, attitudes and economic behavior based on the nation’s ideology. This study can contribute to educational institutions in developing economic learning programs based on the nation’s ideology.